Relationship between Self Compassion and Involvement of Career Single Mothers in Early Childhood Care - Ni'matur Rohmah; Siti Fadjryana Fitroh; Eka Oktavianingsih; Septinda Rima Dewanti; Chan Siaw Leng (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2022)
Self-compassion is an attitude of compassion or compassion for oneself, as well as an attitude to see failure as a great and balanced experience, meanwhile, maternal involvement is the active participation carried out by mothers in the parenting process, including the education of their children's experiences. The purpose of this study was to determine the relationship between self-compassion and the involvement of single career mothers in early childhood care in Gresik Regency. The method used in this research is quantitative correlation with Pearson Product Moment Correlation approach. The sampling technique used is purposive sampling, with the number of respondents being 112 single career mothers in Gresik Regency. The assessment of the research instrument uses a rating scale from a Likert scale with a score of 1-5 with 17 item for variable x and 33 item variable Y. Based on the calculations in the hypothesis test, it can be seen that Ha is accepted and H0 is rejected because it is known that the r value is 0.25 or the KP value is 6.25% and tcount ttable or 3,4960 1.2893. So from these calculations it can be concluded that there is a positive and significant relationship between self-compassion and the involvement of single career mothers, but the degree of relationship or correlation coefficient is in the low category, and mother's involvement is influenced by other factors by 93.25%.